THE INFLUENCE OF COMPENSATION SUITABILITY AND INTERNAL CONTROL SYSTEM TO FRAUDWITH MORALITY AS MODERATING VARIABLE - Junaidi Junaidi; Maulidani Ubaidillah (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
This study aims to observe the effect of compensation suitability and internal control system on fraud. Testing is done directly and indirectly. Indirect influence is made through moderating variable of morality as a moderator of the influence of compensation suitability and internal control system on fraud. Data obtained by purposive sampling. As many as 79 processed data were obtained through the distribution of questionnaires to stakeholders in local government organizations in Pemekasan District of East Java. The parametric test fails because the residual data is not normally distributed even though the outliers’data has been removedfrom the observation. The test was performed using partial least square due to the small sample. Testing the hypothesis proves that the three variables have a significant negative effect on fraud. This confirms the importance of internal control system and compensation suitability as a means of anticipating fraud. Conversely, moderating variable of expected morality may reinforce the nonlinear influence of compensatory suitability and internal control systems not significantly explain fraud.